2009
DOI: 10.1007/s11682-009-9067-2
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Imaging in Alzheimer’s Disease and Other Dementias

Abstract: With the advent of new therapeutic strategies aimed at reducing β-amyloid (Aβ) burden in the brain to potentially prevent or delay functional and irreversible cognitive loss, there is increased interest in developing agents that allow assessment of Aβ burden in vivo. Molecular neuroimaging techniques such as positron emission tomography (PET), in conjunction with related biomarkers in plasma and cerebrospinal fluid, are proving valuable in the early and differential diagnosis of Alzheimer's disease (AD). (11)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 159 publications
(222 reference statements)
0
17
0
Order By: Relevance
“…Many of the molecular probes are derivatives of histological dyes such as Congo Red, thioflavin S and T, Acridine Orange and Chrysamine-G (Coimbra et al, 2006; Fodero-Tavoletti et al, 2009) or other molecules such as styrylbenzene. Two of the most extensively used ligands are [ 11 C]2-(4′-methylaminophenyl)-6-hydroxybenzothiazole (Pittsburgh Compound B or PIB) (Small et al, 2008; Fodero-Tavoletti et al, 2009; Mosconi et al, 2010) and 2-(1-{6-[2-[ 18 F]-fluoroethyl)(methyl)amino]-2-naphthyl}ethylidene) malononitrile ([ 18 F]-FDDNP) (Small et al, 2008; Fodero-Tavoletti et al, 2009; Mosconi et al, 2010). [ 18 F]-FDDNP was the first ligand successfully employed in humans (Rabinovici and Jagust, 2009).…”
Section: Neuroimaging In Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Many of the molecular probes are derivatives of histological dyes such as Congo Red, thioflavin S and T, Acridine Orange and Chrysamine-G (Coimbra et al, 2006; Fodero-Tavoletti et al, 2009) or other molecules such as styrylbenzene. Two of the most extensively used ligands are [ 11 C]2-(4′-methylaminophenyl)-6-hydroxybenzothiazole (Pittsburgh Compound B or PIB) (Small et al, 2008; Fodero-Tavoletti et al, 2009; Mosconi et al, 2010) and 2-(1-{6-[2-[ 18 F]-fluoroethyl)(methyl)amino]-2-naphthyl}ethylidene) malononitrile ([ 18 F]-FDDNP) (Small et al, 2008; Fodero-Tavoletti et al, 2009; Mosconi et al, 2010). [ 18 F]-FDDNP was the first ligand successfully employed in humans (Rabinovici and Jagust, 2009).…”
Section: Neuroimaging In Alzheimer's Diseasementioning
confidence: 99%
“…PIB on the other hand binds with high affinity and specificity to fibrillar Aβ (Coimbra et al, 2006; Fodero-Tavoletti et al, 2009; Mosconi et al, 2010) and its in vivo PET signal correlates strongly with in vitro measures of Aβ burden in post-mortem AD brains (Rabinovici and Jagust, 2009). Studies have demonstrated elevated retention of PIB in the brains of AD patients compared to healthy controls (Coimbra et al, 2006; Small et al, 2008; Mosconi et al, 2010).…”
Section: Neuroimaging In Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Maximum 11 C-PiB uptake in DLBD patients was seen in the anterior or posterior cingulate cortex, followed by the frontal, parietal, temporal, and occipital cortices [27]. Significant 11 C-PiB retention was reported in ∼ 50-60% of individuals with MCI [20]. A meta-analytic sensitivity and specificity of 11 C-PiB for predicting progression from MIC to AD ranged from 83.3 to 100% and from 41.1 to 100%, respectively, with pooled estimates of 94.7 and 57.2%, respectively [28].…”
mentioning
confidence: 93%
“…However, a positive PET can also be seen in normal older individuals as well as in other medical conditions, such as DLBD and cerebral amyloid angiopathy (CAA), and a negative PET can be seen in rare forms of AD with unusual amyloid [20][21][22]. Significant 11 C-PiB retention was reported in ∼ 30% of normal healthy older people, and the mean cortical binding potential for PiB rose in an agedependent manner [20,21]. PiB PET was positive in 18% of persons aged 60-69 years and in 65% of those over 80 years, most strongly in epsilon4 carriers [21].…”
mentioning
confidence: 99%